Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Perilaku Sosial Anak Di Sekolah Dasar - Mahaju Salta, Noviarti (GHAITSA : Islamic Education Journal, 2021)
Emotional behavior can be caused by various problems experienced by children, such as anger, frustration or other negative feelings. Therefore, there is a need for emotional intelligence which leads to decision making for individuals and must be accompanied by spiritual intelligence to develop individuals to think more broadly so that they have high insight in order to make individuals have good behavior in the surrounding environment. This research aims to determine the influence of emotional and spiritual intelligence on children's behavior at school. And the formulation of the problem in this research, "What is the influence of intelligence, emotional and spiritual intelligence on children's social behavior in elementary school?". In this research, descriptive qualitative methods were used, data analysis used interviews, observation and documentation. The subjects of this research were the principal, teachers and students of SDN 71 Bengkulu City. The results of this research were obtained from direct phenomena that occur in objects in the school environment in natural settings. Information obtained from related sources. To shape social behavior with the development of emotional and spiritual intelligence, it is carried out by teachers, such as giving appreciation or applause to children who can answer questions correctly, providing assistance to friends who need it, such as lending pencils or printed books for learning when one of their friends don't have, then apologize or apologize to a friend if you have a problem with that friend. Apart from that, spiritual intelligence also plays an active role in social behavior with teachers showing good behavior in Islam, such as patience, honesty and sincerity. In this way, good social behavior is created in children and will be implemented in their lives in the future.